methyl-ATAC-seq measures DNA methylation at accessible chromatin - Spektor, Roman; Tippens, Nathaniel D.; Mimoso, Claudia A.; Soloway, Paul D. (Genome Research, 2019)
Chromatin features are characterized by genome-wide assays for nucleosome location, protein binding sites, three-dimensional interactions, and modifications to histones and DNA. For example, assay for transposase accessible chromatin sequencing (ATAC-seq) identifies nucleosome-depleted (open) chromatin, which harbors potentially active gene regulatory sequences; and bisulfite sequencing (BS-seq) quantifies DNA methylation. When two distinct chromatin features like these are assayed separately in populations of cells, it is impossible to determine, with certainty, where the features are coincident in the genome by simply overlaying data sets. Here, we describe methyl-ATAC-seq (mATAC-seq), which implements modifications to ATAC-seq, including subjecting the output to BS-seq. Merging these assays into a single protocol identifies the locations of open chromatin and reveals, unambiguously, the DNA methylation state of the underlying DNA. Such combinatorial methods eliminate the need to perform assays independently and infer where features are coincident.